Does language affect memory for object position? A crosslinguistic comparison. Issue 4 (2nd October 2018) - Bosse, Solveig; Papafragou, Anna
ABSTRACT: We present an experimental investigation of the influence of language on spatial memory. German and English differ in how they encode the axial position (standing vs. lying) of an inanimate figure object which is supported by a ground object. In a series of four experiments, we show that German and English speakers' ability to detect changes in axial position during recognition memory tasks is unaffected by this linguistic difference. Even when participants are required to use language to encode the spatial scenes, later recognition memory performance does not differ between the two language groups. We discuss implications of these findings for the relation between language and cognition.